'Endless wars of altruism'? Human rights, humanitarianism and the Syrian war. Issue 5 (28th May 2019) - Dixon, Paul
ABSTRACT: This article argues that Liberal Hawks have used a Human Rights-based narrative to legitimise war in the post-Cold War era. Liberal Hawks in the UK and the USA have allied with Neoconservatives to form a powerful coalition to advocate for 'humanitarian intervention' to 'protect human rights' and 'prevent genocide'. A particular interpretation of a human rights-based approach has been used to justify war by presenting these rights as natural, absolute, universal and non-political. Those in the human rights movement have advocated this interpretation but it has also become influential on humanitarian NGOs. The impact of this RBA is that humanitarian NGOs has generally become more ambitious and shifted from the provision of needs-based, immediate relief to the advocacy of military intervention to sustain longer-term transformation through democratisation and state-building. The capture of humanitarianism by this 'rights-based' narrative has created a powerful Liberal Hawk argument for war as a policy instrument. The arguments of Labour Hawks, Hilary Benn MP and Jo Cox MP, for more extensive British military involvement in Syria in 2015 are used to show how arguments to end human rights abuses and provide humanitarian assistance are effectively arguments to escalate war.